THE EFFECTS OF VISUAL MAPPING AND SCIENCE-RELATED ATTITUDES ON STUDENTS’ CRITICAL THINKING AND PROBLEM SOLVING SKILLS - Muhammad Jamhari; Syarifuddin Syarifuddin; Herbert Sipahutar (Universitas Islam Negeri Ar-Raniry, 2020)
The aims of this study were to find out: (1) the effects of visual mapping on students’ critical thinking skills, (2) the effects of science-related attitudes on students’ critical thinking skills, (3) the interactions between visual mapping and science-related attitudes on students’ critical thinking skills, (4) the effects of visual mapping on students’ problem solving skills, (5) the effects of science-related attitudes on students’ problem solving skills, and (6) the interactions between visual mapping and science-related attitudes on students’ problem solving skills. This study was conducted at MAN 1 Tanjung Pura, totally 141 students. It was a quasi-experimental technique by using a pretest-posttest experimental group with 4x2 factorial design. The technique of data analysis was processed by the Two-Way ANOVA and followed by Duncan’s Multiple Range Test. The results showed that: (1) there were the significant effects of visual mapping on students’ critical thinking skills (F=87.082; P=0.000), (2) there were the significant effects of science-related attitudes on students’ critical thinking skills (F=2.493; P=0.040), (3) there were the interactions between visual mapping and science-related attitudes on students’ critical thinking skills (F=2.037; P=0.000), (4) there were the significant effects of visual mapping on students’ problem solving skills (F=94.214; P=0.000), (5) there were the significant effects of science-related attitudes on students’ problem solving skills (F=3.397; P=0.031), and (6) there were the interactions between visual mapping and science-related attitudes on students’ problem solving skills (F=2.195; P=0.000).